Unexplained Isolated AST Elevation: A Case of Macro-AST and a Brief Review of Literature - Abdullah Sultany; Adishwar Rao; Amlish Gondal; Abdullah M Al-Qudah; Tsu Yang; Chaitanya K Chandrala; Michael Georgetson (The Guthrie Clinic Journal of Medicine, 2026)
Abstract Background: Macro-aspartate aminotransferase (macro-AST) is a benign phenomenon caused by the formation of high-molecular-weight complexes, typically between aspartate aminotransferase (AST) and immunoglobulins, that results in isolated serum AST elevation without evidence of actual liver or muscle injury. Although patients remain asymptomatic and other liver tests are normal, unrecognized macro-AST may trigger extensive, sometimes invasive, diagnostic evaluations. Case Report: We report the case of a 65-year-old female with persistently elevated AST (peak: 139 U/L), which was confirmed as macro-AST via polyethylene glycol (PEG) precipitation, with AST normalizing to 17 U/L postprecipitation. Discussion: We provide a brief literature review of 17 published macro-AST cases confirmed by PEG precipitation. Our case underscores the importance of considering macro-AST in patients with unexplained isolated AST elevation, because early recognition prevents unnecessary invasive procedures. Conclusions: Increased awareness of macro-AST can help prevent unnecessary workups and invasive procedures.